Supporting undergraduate learning through the collaborative promotion of e-journals by library and academic departments. Electronic journals, E-journals, Higher education, (Information Research: An International Electronic Journal)
The introduction of electronic journals into Higher Education institutions in the United Kingdom has been relatively well documented, in terms of their purchase, management and uptake. However, the impact on learning, other than trends in usage and some indications of students' and researchers' attitudes, has not been quantified. This paper evaluates a project designed with the primary aim of testing a hypothesis that learning can be enhanced by promoting the use of e-journals. It was run jointly by a member of the library staff and an academic within the Business School. A 'research quotient' was developed to measure a student's ability to carry out appropriate research to support their learning. Research quotient scores were analysed along with journal bibliographic citations in students' assignments. Analysis of the results indicated that effective collaboration between academic and library staff, the timely embedding of e-journal induction into the learning process and associating it with the assessment process, can significantly enhance the learning of students. It was also recognised that students need be encouraged to see beyond assignments and adopt an holistic approach to learning.